P-305 Uterine contractile function across the menstrual cycle in healthy women: an exploration of objective reference values of sub-endometrial motion using speckle tracking. (30th June 2022) - Schoot, B; Rees, C; Huang, Y; De Boer, A; Wessels, B; Huppelschoten, D; Zizolfi, B; Di Spiezio Sardo, A; Christoforidos, N; Van Vliet, H; Mischi, M
Abstract: Study question: To explore the characteristics of normal uterine contractile function across the menstrual cycle in healthy women using a novel quantitative ultrasound method. Summary answer: We confirm reproducible differences in uterine contractility across the menstrual cycle; highest activity seen in the periovulatory phase, and lowest in the late luteal phase. What is known already: Uterine peristalsis is the rhythmic, wave-like motion of the subendometrial layer of the uterus. Various subjective methods using visual interpretation suggest that uterine peristalsis features are different in the various stages of the menstrual cycle, and they are thought to be important for fertility. However, no method has been developed which can assess all uterine contraction features simultaneously. Recently, a new automated quantitative method to measure uterine contractility was validated in IVF patients to analyse uterine peristalsis on transvaginal ultrasound recordings with speckle-tracking. With this method a new contraction feature – coordination – can be assessed alongside frequency, direction, amplitude. Study design, size, duration: Multi-centre observational prospective cohort study carried out in the outpatient gynaecology department of the Catharina Hospital in Eindhoven, the Netherlands, the University of Naples, Federico II, Naples, Italy and Embryolab Fertility centre in Thessaloniki, Greece. Patients were included from September 2020 up to January 2022. Primary outcomes were the contraction frequency (contractions/minute), amplitude, direction (Cervix-to-fundus, Fundus-to-cervix), and coordination. Participants/materials, setting, methods: 63 women were included from the gynaecological department of participating centres. Women were included if they were ≥18 years of age, premenopausal and had a normal, natural menstrual cycle. A normal cycle was defined as: regular (duration ± 28 days), no dysmenorrhea, no menometrorrhagia. Transvaginal ultrasounds were performed during the menstrual phase (M), late follicular (periovulatory) phase (LF), early luteal phase (EL, ovulation + 3 days) and/or late luteal phase (LL, ovulation + 7 days). Main results and the role of chance: Uterine contractility features were extracted from the gathered ultrasound recordings using a quantitative dedicated speckle tracking algorithm previously developed by our group. Each patient underwent a four-minute ultrasound of the uterus in mid-sagittal section. Patients had a mean age of 32 years, cycle duration of 27.8, and BMI of 23.0. The majority of women was nulliparous. The majority of uterine contraction features differed significantly between menstrual cycle phases. Contraction frequency was highest in the LF phase and lowest in the M and LL phases (1.55 vs. 1.28/min, p = 0.001). A trend was found for contractions during the periovulatory and early luteal phases contractions to travel mainly from cervix-to-fundus direction, whilst the menstrual phase showed contractions mainly from the fundus to cervix (p > 0.05). No significant difference between phases was found for contraction amplitude. Contraction coordination (simultaneous contraction of the anterior and posterior walls in the same direction) was highest in the periovulatory phase (p = 0.002). Our results are in line with with previous published studies using subjective visual inspection. Limitations, reasons for caution: This is the first study investigating contraction coordination as a specific feature of uterine peristalsis. Not all patients were available for multiple ultrasounds during the same cycle, thereby a within-subjects comparison of the uterine contractions was not possible. Wider implications of the findings: We explored further implementation of a quantitative method of uterine peristalsis measurement. Our investigation of a novel contraction characteristic - coordination - opens up possibilities for research and a potential etiological/treatment target. Further research using this method and suggested reference values will provide insight into contraction characteristics in abnormal uteri. Trial registration number: NCT02310802